Diaphragm for alkaline water electrolysis and its manufacturing method
Patent Information
- Application Number
- JP2021083402
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-05-17
AI Technical Summary
【0011】 本発明のアルカリ水電解用隔膜は、熱アルカリ中におけるイオン伝導性の安定性に優れる。そのため、アルカリ水電解装置に本発明のアルカリ水電解用隔膜を用いれば、長期間安定して高純度の水素ガスを製造することができる。
Smart Images

Figure 0007641817000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a diaphragm for alkaline water electrolysis and a method for producing the same. More specifically, the present invention relates to a diaphragm for alkaline water electrolysis having excellent stability of ion conductivity in hot alkali, and a method for producing the same. [Background technology]
[0002] Water electrolysis (also called "electrolysis") is known as one of the industrial methods for producing hydrogen gas, and is generally carried out by applying an electric current to water to which an electrolyte such as sodium hydroxide or potassium hydroxide has been added to increase the electrical conductivity. For such water electrolysis, an electrolytic cell is used which has an anode chamber and a cathode chamber, each of which is separated by a diaphragm.
[0003] Water electrolysis is carried out by the movement of electrons (or ions). Therefore, the diaphragm is required to have high ionic conductivity in order to efficiently carry out the electrolysis reaction. Furthermore, water electrolysis is carried out using alkaline water with a high concentration of about 30%, at 80 to 100°C, and in some cases under high pressure of 1 MPa or more, so heat resistance, alkali resistance, etc. are also required to maintain high ionic conductivity.
[0004] As a membrane used for electrolysis of water, various porous membranes manufactured by the non-solvent induced phase separation method (NIPS method) have been known so far. In the production of a porous membrane by the non-solvent induced phase separation method, the pore structure such as pore size is affected by the replacement rate of the solvent and the non-solvent, and it is generally known that, for example, by reducing the replacement rate of the solvent and the non-solvent, coarse pores such as macrovoids are unlikely to be formed on the surface of the porous membrane. It is known that the replacement rate of the solvent and the non-solvent is affected by the addition of hydrophilic additives such as polyvinylpyrrolidone and lithium chloride to the coating composition used to prepare the porous membrane, and by the hydrophilization and thickening of the coating composition by the hydrophilic additives (for example, Non-Patent Document 1, Non-Patent Document 2).
[0005] In addition, in a diaphragm used for electrolysis of water, it is known that inorganic particles are contained in the diaphragm made of a resin in order to increase the ionic conductivity of the diaphragm (for example, Patent Document 1 and Patent Document 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2019 / 021774 [Patent Document 2] JP 2020-169349 A [Non-patent literature]
[0007] [Non-Patent Document 1] Desalination,2006,Vol.192,p.190-197 [Non-Patent Document 2] Desalination,1988,Vol.68,p.167-177 Summary of the Invention [Problem to be solved by the invention]
[0008] According to studies by the present inventors, a diaphragm having a porous layer containing inorganic particles has excellent ionic conductivity, but when the diaphragm having the porous layer is used as a diaphragm for alkaline water electrolysis, there is a problem in that the ionic conductivity is likely to vary over time. The present invention has been made in view of the above problems, and an object of the present invention is to provide a diaphragm for alkaline water electrolysis having excellent stability of ion conductivity in hot alkali. [Means for solving the problem]
[0009] The present inventors have studied diaphragms having a porous layer containing inorganic particles and have found that the size and content of macrovoids contained in the porous layer are deeply involved in the stability of ion conductivity. They have also found that gas permeability per unit thickness, which is an index of the porous structure of a diaphragm, also affects the stability of ion conductivity. They have found that by using a composition having specific viscosity characteristics as a composition containing inorganic particles for forming a porous layer, the generation and growth of macrovoids are suppressed, and a diaphragm having a porous layer with a controlled porous structure is obtained, and the obtained diaphragm has excellent stability of ion conductivity, and have completed the present invention.
[0010] That is, the diaphragm for alkaline water electrolysis of the present invention is a diaphragm for alkaline water electrolysis having a porous layer containing an organic polymer and inorganic particles, the porous layer is a layer that constitutes at least one surface of the diaphragm, and the content of macrovoids having a major axis of 30 μm or more in a cross section in the thickness direction of the porous layer is 40% or less; X represented by the following formula (1) is 0.6 or more. The diaphragm for alkaline water electrolysis is characterized in that X = membrane air permeability (sec) / membrane thickness (μm) (1) Effect of the Invention
[0011] The diaphragm for alkaline water electrolysis of the present invention has excellent stability of ion conductivity in hot alkali. Therefore, use of the diaphragm for alkaline water electrolysis of the present invention in an alkaline water electrolysis apparatus enables stable production of high-purity hydrogen gas for a long period of time. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a conceptual diagram for explaining the maximum shear rate during coating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention will be described in detail below. In addition, a combination of two or more of the individual preferred embodiments of the present invention described below is also a preferred embodiment of the present invention.
[0014] 1. Diaphragms for alkaline water electrolysis A diaphragm for alkaline water electrolysis, which is a first embodiment of the present invention, will be described. The diaphragm for alkaline water electrolysis of the present invention is a diaphragm for alkaline water electrolysis having a porous layer containing an organic polymer and inorganic particles, the porous layer is a layer that constitutes at least one surface of the diaphragm, and the content of macrovoids having a major axis of 30 μm or more in a cross section in the thickness direction of the porous layer is 40% or less; X represented by the following formula (1) is 0.6 or more. It is characterized by: X = membrane air permeability (sec) / membrane thickness (μm) (1) In this specification, a porous layer containing an organic polymer and inorganic particles is also simply referred to as a porous layer. The diaphragm for alkaline water electrolysis of the present invention comprises a porous layer comprising an organic polymer and inorganic particles as a layer constituting at least one of its surfaces. That is, the porous layer constituting the diaphragm for alkaline water electrolysis of the present invention is a layer constituting at least one of the surfaces of the diaphragm. The presence of the porous layer allows the diaphragm to be impregnated with a large amount of electrolytic solution and exhibits ion permeability.
[0015] The diaphragm for alkaline water electrolysis of the present invention may be composed only of the porous layer, or may further include a porous support. The inclusion of the porous support improves the strength of the porous layer, thereby improving the strength of the diaphragm for alkaline water electrolysis and suppressing damage to the ion permeable membrane during electrolysis. The porous support is preferably a sheet-like member.
[0016] When the diaphragm for alkaline water electrolysis of the present invention comprises a porous support, the form thereof is not particularly limited as long as the porous layer constitutes at least one surface of the diaphragm. For example, preferred embodiments of the configuration of the diaphragm for alkaline water electrolysis include a form (1) in which a porous layer is laminated on one surface of a porous support, and a form (2) in which porous layers are laminated on both surfaces of a porous support.
[0017] Furthermore, form (1a) is also a preferred embodiment of form (1), in which an organic polymer and / or inorganic particles similar to the organic polymer and inorganic particles constituting the porous layer are contained in part or all of the interior of the porous support. Similarly, form (2a) is also a preferred embodiment, in which an organic polymer and / or inorganic particles similar to the organic polymer and inorganic particles constituting at least one of the porous layers are contained in part or all of the interior of the porous support.
[0018] Among the above-mentioned form (1a), a preferred embodiment is form (1b), in which the porous support has the above-mentioned porous layer on one side thereof, and a layer (impregnated layer) impregnated with the same component as the material constituting the porous layer is provided in a part or all of the interior of the porous support from the interface between the porous layer and the porous support. Similarly, among the above-mentioned form (2a), there is also a form (2b) in which the above-mentioned porous layers are provided on both sides of the porous support, and a layer (impregnated layer) is provided in part or all of the interior of the porous support from the interface between the porous layers and the porous support, the layer being impregnated with the same component as the material constituting at least one of the porous layers.
[0019] Among these, the diaphragm for alkaline water electrolysis of the present invention is preferably the above-mentioned form (1a), (1b), (2a) or (2b) in that the strength of the diaphragm is further increased, and among these, form (1b) or (2b) is more preferable, and form (1b) is even more preferable.
[0020] As described above, in the diaphragm for alkaline water electrolysis of the present invention, at least one porous layer constituting a surface layer has a content of macrovoids having a major axis of 30 μm or more in a cross section in the thickness direction of the porous layer of 40% or less. The condition that "the content of macrovoids having a major axis of 30 μm or more in a cross section in the thickness direction of the porous layer is 40% or less" is also referred to as condition (Y). The content of macrovoids having a major axis of 30 μm or more is sometimes simply referred to as the macrovoid content.
[0021] When the diaphragm for alkaline water electrolysis of the present invention comprises a porous support, at least one of the porous layers constituting the surface of the diaphragm for alkaline water electrolysis of the present invention satisfies condition (Y), regardless of the form of the porous support. When the diaphragm for alkaline water electrolysis of the present invention has porous layers constituting the surfaces of the diaphragm for alkaline water electrolysis on both sides, it is preferable that all of the porous layers satisfy condition (Y).
[0022] In the present invention, the macrovoid means a void having a major axis of 10 μm or more and a minor axis of 5 μm or more. The major axis and minor axis are determined as follows. That is, a cross section of the diaphragm for alkaline water electrolysis of the present invention cut in the thickness direction, i.e., in the direction perpendicular to the surface of the diaphragm, is observed with a field emission scanning electron microscope (FE-SEM) to obtain a cross-sectional image of the porous layer to be measured. The imaging magnification using the field emission scanning electron microscope is not particularly limited, but taking into consideration the size of macrovoids, etc., it is preferably 100 to 2000 times, and more preferably 200 to 1000 times.
[0023] The above-mentioned major axis and minor axis are determined by determining the thickness direction length (Lt) and the plane direction length (Lf) from the void image observed in the obtained cross-sectional observation image, and the larger of (Lt) and (Lf) is defined as the major axis and the smaller is defined as the minor axis.
[0024] The thickness direction length (Lt) is the length in the thickness direction of the membrane, i.e., the direction perpendicular to the membrane surface, and specifically, the distance between the point of the void closest to the membrane (porous membrane) surface and the point closest to the opposite surface in the thickness direction of the membrane (perpendicular to the membrane surface) is the thickness direction length (Lt) of the void. The area (S) of the void divided by the thickness direction length (Lt) is the planar length (Lf) of the void. The larger of the thus obtained (Lt) and (Lf) is the major axis (Lb) of the void, and the smaller is the minor axis (Ls) of the void.
[0025] The thickness direction length (Lt) and area (S) of the void can be determined by extracting the void portion as a dark area from the cross-sectional observation image using image analysis software (eg, Scion Image, manufactured by Scion Corporation).
[0026] The voids thus determined have a major axis of 10 µm or more and a minor axis of 5 µm or more and are referred to as macrovoids. It is important that in the diaphragm for alkaline water electrolysis of the present invention, at least one porous layer constituting a surface layer thereof has a content of macrovoids having a major axis of 30 µm or more of 40% or less.
[0027] The macrovoid content means the ratio (percentage) of the total area of macrovoids having a major axis of 30 μm or more to the area of the porous layer in the cross-sectional observation image. Usually, the measurement area in the cross-sectional observation image is the area surrounded by the thickness (total thickness) of the porous layer in the thickness direction of the membrane (porous membrane) and a line segment 400 μm long in the surface direction of the membrane (porous layer).
[0028] Then, using image analysis software (e.g., Scion Image, manufactured by Scion), the total area (Sy) of macrovoids whose major axis is 30 μm or more (i.e., the sum of the individual areas of the macrovoids) and the area (St) of the measurement region are determined, and the ratio (percentage) of (Sy) to (St) is calculated. The obtained value is the content of macrovoids whose major axis is 30 μm or more.
[0029] The porous layer in the diaphragm for alkaline water electrolysis of the present invention has a content of macrovoids having a major axis of 30 µm or more, determined as described above, of 40% or less. From the viewpoint of the diaphragm for alkaline water electrolysis of the present invention also having excellent strength properties such as tensile strength, the macrovoid content is preferably 35% or less, more preferably 30% or less, and even more preferably 25% or less.
[0030] For the same reason, the content of macrovoids having a major axis of 20 μm or more, determined in the same manner, is preferably 40% or less, more preferably 35% or less, even more preferably 30% or less, and most preferably 25% or less.
[0031] In the diaphragm for alkaline water electrolysis of the present invention, X represented by the following formula (1) is 0.6 or more: X = membrane air permeability (sec) / membrane thickness (μm) (1) In formula (1), the air permeability of the diaphragm means the air permeability of the diaphragm. The air permeability can be determined by a conventionally known measurement method, and a value measured using a commercially available measurement device can be adopted. The gas used during measurement is air. For example, the air permeability can be measured using an Oken air permeability tester (manufactured by Asahi Seiko Co., Ltd., model number: EGBO), and the measured value can be used as the air permeability of the diaphragm for alkaline water electrolysis of the present invention. It is preferable to measure multiple points, for example three points, arbitrarily selected for one sample, and use the average value as the air permeability.
[0032] In formula (1), the thickness of the diaphragm means the thickness of the diaphragm for alkaline water electrolysis of the present invention. The measurement method is a value measured with a micrometer. Usually, it is preferable to measure at multiple locations, for example, 10 locations, and to use the average value as the thickness of the diaphragm. As the micrometer, it is preferable to use a commercially available product, for example, a Digimatic Micrometer (manufactured by Mitutoyo Corporation).
[0033] X can be determined using the air permeability (seconds) and membrane thickness (μm) of the diaphragm for alkaline water electrolysis of the present invention measured by the above-mentioned measurement method. X is more preferably 0.65 or more, further preferably 0.70 or more, and particularly preferably 0.75 or more. On the other hand, there is no particular upper limit for X, but it is preferably 4.00 or less, more preferably 3.50 or less.
[0034] When measuring the macrovoid content, and the air permeability and membrane thickness for determining X for the diaphragm for alkaline water electrolysis of the present invention, any part of the diaphragm can be used as a measurement sample. When the diaphragm is in a sheet-like form, it is preferable to select a measurement site (to obtain a measurement sample) within the range of a circle drawn around the center of the sheet and having an area that accounts for 80% of the total area of the sheet in the plane direction.
[0035] The selected site may be one, but is preferably three or more, and more preferably five. It is preferable to measure the macrovoid content, X, for each selected site and to determine the simple average value of the macrovoid content, X, in the diaphragm.
[0036] The porous layer comprises an organic polymer and inorganic particles. Examples of the organic polymer include fluorine-based resins, olefin-based resins, and aromatic hydrocarbon-based resins.
[0037] Examples of the fluorine-based resin include ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, polyvinyl fluoride, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polychlorotrifluoroethylene, tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer, and the like. Examples of the olefin resin include polyethylene, polypropylene, polybutene, and polymethylpentene. Examples of the aromatic hydrocarbon resin include polyethylene terephthalate, polybutylene terephthalate, polybutylene naphthalate, polystyrene, polysulfone, polyethersulfone, polyphenylene sulfide, polyphenylsulfone, polyarylate, polyetherimide, polyimide, and polyamideimide.
[0038] Among these, the organic polymer is preferably an aromatic hydrocarbon resin in view of excellent heat resistance, pressure resistance and alkali resistance, more preferably at least one selected from the group consisting of polysulfone, polyethersulfone and polyphenylsulfone, and even more preferably polysulfone in view of ease of production of the diaphragm. The organic polymers may be used alone or in combination of two or more.
[0039] The content of the organic polymer is preferably 5 to 40 mass% relative to 100 mass% of the diaphragm for alkaline water electrolysis. When the content of the organic polymer is within the above range, elution of inorganic components from the diaphragm in an alkaline solution can be suppressed. The content of the organic polymer is more preferably 7 mass% or more, even more preferably 10 mass% or more, more preferably 35 mass% or less, and even more preferably 30 mass% or less, relative to 100 mass% of the diaphragm for alkaline water electrolysis.
[0040] When the diaphragm for alkaline water electrolysis does not contain a porous support described below, the content of the organic polymer is preferably 28 to 40 mass% relative to 100 mass% of the diaphragm for alkaline water electrolysis. When the content of the organic polymer is within the above range, a void structure controlled by the organic polymer is easily formed in the diaphragm. The content of the organic polymer is more preferably 31 mass% or more, more preferably 38 mass% or less, and even more preferably 36 mass% or less, relative to 100 mass% of the diaphragm for alkaline water electrolysis.
[0041] Furthermore, when the diaphragm for alkaline water electrolysis contains a porous support described below, the content of the organic polymer is preferably 5 to 35 mass% relative to 100 mass% of the diaphragm for alkaline water electrolysis. When the content of the organic polymer is within the above range, a void structure controlled by the organic polymer is easily formed in the diaphragm. The content of the organic polymer is more preferably 8 mass% or more, even more preferably 12 mass% or more, even more preferably 17 mass% or more, and more preferably 30 mass% or less, even more preferably 25 mass% or less, even more preferably 23 mass% or less, and particularly preferably 21 mass% or less, relative to 100 mass% of the diaphragm for alkaline water electrolysis.
[0042] Examples of the inorganic particles include metal hydroxides or oxides such as magnesium, zirconium, titanium, zinc, aluminum, and tantalum, sulfates such as calcium, barium, lead, and strontium, nitrides such as titanium, zirconium, and hafnium, and carbides such as titanium, zirconium, and hafnium. The inorganic particles may contain only one type, or two or more types. Among these, from the viewpoint of improving ion permeability, metal hydroxides or metal oxides are preferred, magnesium hydroxide, zirconium hydroxide, titanium hydroxide, zirconium oxide and titanium oxide are more preferred, magnesium hydroxide, zirconium hydroxide, titanium hydroxide and titanium oxide are even more preferred, magnesium hydroxide, zirconium hydroxide and titanium hydroxide are even more preferred, and magnesium hydroxide is particularly preferred.
[0043] The inorganic particles may be surface-untreated or surface-treated, for example, by known surface treatments using a silane coupling agent, stearic acid, oleic acid, phosphoric acid ester, or the like.
[0044] The shape of the inorganic particles is not particularly limited, and may be any of irregular, granular, granular, plate-like (e.g., flake, hexagonal plate-like), fibrous, etc. Among these, in terms of excellent adhesion to resin, the inorganic particles are preferably granular or plate-like, more preferably plate-like, and even more preferably flaky. Furthermore, in terms of a dense structure and improved membrane strength, the inorganic particles are preferably plate-like, and more preferably flaky.
[0045] The inorganic particles preferably have an average particle size of 0.05 μm or more and 2.0 μm or less, in order to provide a dense structure and improve the strength of the membrane, and more preferably have an average particle size of 0.08 μm or more and even more preferably 0.1 μm or more, more preferably 1.5 μm or less and even more preferably 1 μm or less.
[0046] The above-mentioned average particle size is the volume average particle size (D50) obtained by measuring the particle size distribution by the laser diffraction method. Specifically, the average particle size is measured by using a laser diffraction / scattering type particle size distribution measuring device (for example, "Model LA-920" manufactured by Horiba, Ltd.), and the median diameter (D50) in the volume-based particle size distribution is taken as the average particle size. Note that the particles are mixed in ethanol and dispersed by ultrasonic irradiation to be the measurement sample.
[0047] The inorganic particles preferably have an aspect ratio of 2.0 to 8.0. When the aspect ratio is within the above range, a membrane having even more excellent ion permeability and excellent uniformity can be obtained. The aspect ratio is more preferably 2.5 to 7.0, and further preferably 3.0 to 6.0.
[0048] The aspect ratio means the ratio [(a) / (b)] of the longest diameter (a) to the shortest diameter (b), and can be obtained by observing inorganic particles with a SEM, measuring the ratio [(a) / (b)] of the longest diameter (a) to the shortest diameter (b) of each particle for any 10 particles in the obtained image using analysis software, etc., and calculating the simple average value of these ratios as the aspect ratio of the particle. Usually, it is preferable to use the shortest diameter (b) as the shortest diameter among the diameters that pass through the midpoint of the longest diameter (a) and are perpendicular to the longest diameter.
[0049] As the above-mentioned longest diameter (a), for example, when the particle has a plate-like shape such as a flaky or hexagonal plate-like shape, the longest diameter of the plate surface of the particle is used, and when the particle has a fibrous shape, the length of the fiber is used. As the shortest diameter (b), for example, when the particle shape is a plate shape such as a thin plate or a hexagonal plate, the thickness of the particle is used, and when the particle shape is a fiber shape, the thickness of the fiber is used. As the thickness of the particle and the thickness of the fiber, it is preferable to use the thickness and the thickness at the midpoint of the longest diameter a, respectively.
[0050] Among these, magnesium hydroxide is preferred as the inorganic particles in that it has particularly excellent alkali resistance and durability and can provide a diaphragm for alkaline water electrolysis at relatively low cost. The magnesium hydroxide that can be used in the present invention preferably has the above-mentioned average particle size and aspect ratio, respectively.
[0051] The magnesium hydroxide preferably has a crystallite diameter of 35 nm or more in a direction perpendicular to the (110) plane as measured by X-ray diffraction. When the crystallite diameter in the direction perpendicular to the (110) plane is within the above-mentioned range, the ion permeability and uniformity of the membrane are further improved. The crystallite diameter in the direction perpendicular to the (110) plane is preferably 40 nm or more, more preferably 50 nm or more, even more preferably 60 nm or more, and particularly preferably 65 nm or more. The upper limit of the crystallite diameter in the direction perpendicular to the (110) plane is not particularly limited, but is usually, for example, 400 nm or less, preferably 350 nm or less, and more preferably 300 nm or less.
[0052] The magnesium hydroxide preferably has a crystallite size of 15 nm or more in the direction perpendicular to the (001) plane as measured by X-ray diffraction. The crystallite diameter in the direction perpendicular to the (001) plane is more preferably 18 nm or more, even more preferably 21 nm or more, and particularly preferably 24 nm or more. The upper limit of the crystallite diameter in the direction perpendicular to the (001) plane is not particularly limited, but is usually, for example, 300 nm or less, preferably 250 nm or less, and more preferably 200 nm or less. The crystallite diameter can be obtained by measuring the X-ray diffraction pattern of magnesium hydroxide particles by powder X-ray diffraction method, and calculating the crystallite diameter (crystallite diameter in the direction perpendicular to the lattice plane) using Scherrer's formula from the spread (half-width) of the diffraction line assigned to the target lattice plane.
[0053] As a method for obtaining magnesium hydroxide having the above-mentioned specific crystallite size range, for example, the following method can be mentioned. Magnesium hydroxide is prepared by hydration reaction using an aqueous solution of magnesium salt (magnesium chloride, magnesium nitrate, etc.) or an aqueous dispersion of magnesium oxide obtained by a conventional method as a raw material and adding an alkaline substance (lithium hydroxide, sodium hydroxide, calcium hydroxide, ammonia water, etc.). At this time, by adding an organic acid such as formic acid, acetic acid, propionic acid, etc., a polybasic acid such as nitric acid, sulfuric acid, or a mixture thereof, the solubility of the generated magnesium hydroxide can be adjusted, and by appropriately adjusting the temperature (e.g., 150°C to 270°C) and time (e.g., 30 minutes to 10 hours) of the hydrothermal reaction, particles with different crystallite sizes can be prepared. The more the amount of acid added, the more the crystal growth advances and the larger the crystallite size. Also, the higher the temperature of the hydrothermal reaction and the longer the time, the more the crystal growth advances and the larger the crystallite size.
[0054] In the present invention, general commercial products can be used as inorganic particles. For example, commercially available magnesium hydroxide products that can be used in the present invention include 200-06H manufactured by Kyowa Chemical Industry Co., Ltd., UP650-1 manufactured by Ube Materials Co., Ltd., MAGSTAR #20 manufactured by Tateho Chemical Industry Co., Ltd., and #200 manufactured by Konoshima Chemical Co., Ltd.
[0055] The content of the inorganic particles is preferably 30 to 90 mass% relative to 100 mass% of the diaphragm for alkaline water electrolysis. When the content of the inorganic particles is within the above range, the diaphragm for alkaline water electrolysis has excellent ion permeability. The content of the inorganic particles is more preferably 35 mass% or more, even more preferably 40 mass% or more, more preferably 85 mass% or less, and even more preferably 80 mass% or less, relative to 100 mass% of the diaphragm for alkaline water electrolysis.
[0056] When the diaphragm for alkaline water electrolysis does not contain a porous support described below, the content of the inorganic particles is preferably 50 to 90 mass% relative to 100 mass% of the diaphragm for alkaline water electrolysis. The content of the inorganic particles in this range can make the structure dense and improve the strength of the diaphragm. The content of the inorganic particles is more preferably 85 mass% or less, even more preferably 80 mass% or less, more preferably 55 mass% or more, and even more preferably 60 mass% or more, relative to 100 mass% of the diaphragm for alkaline water electrolysis.
[0057] Furthermore, when the diaphragm for alkaline water electrolysis contains a porous support described below, the content of the inorganic particles is preferably 30 to 50 mass% relative to 100 mass% of the diaphragm for alkaline water electrolysis. The content of the inorganic particles in this range can make the structure dense and improve the strength of the diaphragm. The content of the inorganic particles is more preferably 32 mass% or more, even more preferably 34 mass% or more, and more preferably 46 mass% or less, even more preferably 42 mass% or less, and even more preferably 39 mass% or less, relative to 100 mass% of the diaphragm for alkaline water electrolysis.
[0058] The porous layer preferably contains 40 to 80 parts by mass, more preferably 45 to 70 parts by mass, and even more preferably 45 to 60 parts by mass of the organic polymer per 100 parts by mass of the inorganic particles. When the contents of the inorganic particles and the organic polymer are within the above-mentioned ranges, the strength of the diaphragm can be improved, and a diaphragm having a mass reduction rate within a predetermined range is more likely to be obtained. Furthermore, the diaphragm for alkaline water electrolysis preferably contains 40 to 80 parts by mass, more preferably 45 to 70 parts by mass, and even more preferably 45 to 60 parts by mass of the organic polymer per 100 parts by mass of the inorganic particles.
[0059] The thickness of the porous layer is not particularly limited, but is usually preferably 30 to 2000 μm. When the diaphragm for alkaline water electrolysis of the present invention consists of only a porous layer, the thickness of the porous layer is preferably 30 to 2000 μm, more preferably 100 μm or more, and even more preferably 200 μm or more. The upper limit is more preferably 1000 μm or less, and even more preferably 500 μm or less. When the diaphragm for alkaline water electrolysis of the present invention comprises a porous support, the thickness of the porous layer is preferably 30 to 1000 μm, more preferably 500 μm or less, even more preferably 100 μm or less, and most preferably 60 μm or less.
[0060] The method for measuring the thickness of the porous layer is not particularly limited, but the thickness can be determined from a microscopic image obtained by observing a cross section of the diaphragm for alkaline water electrolysis of the present invention cut in the thickness direction, i.e., in the direction perpendicular to the surface of the diaphragm, with a field emission scanning electron microscope (FE-SEM). Typically, the thickness is measured at any multiple positions, for example, five positions, and the average value of the measurements can be used as the thickness of the porous layer.
[0061] When the diaphragm for alkaline water electrolysis consists only of a porous layer, the thickness can be measured using a commercially available measuring device, as in the case of the thickness of the diaphragm for alkaline water electrolysis of the present invention. For example, a value measured using a Digimatic Micrometer (manufactured by Mitutoyo Corporation) can be used. The thickness can be measured at any 5 or more points (e.g., 10 points) and the average value can be used as the thickness of the porous layer.
[0062] Examples of the material of the porous support include resins such as polyethylene, polypropylene, polysulfone, polyethersulfone, polyphenylsulfone, polyphenylene sulfide, polyketone, polyimide, polyetherimide, and fluorine-based resins. These may be used alone or in combination of two or more. Among them, in terms of excellent heat resistance and alkali resistance, it is preferable to contain at least one resin selected from the group consisting of polypropylene, polyethylene, and polyphenylene sulfide, and it is more preferable to contain at least one resin selected from the group consisting of polypropylene and polyphenylene sulfide.
[0063] Examples of the form of the porous support include nonwoven fabric, woven fabric, mesh, porous membrane, or a mixture of nonwoven fabric and woven fabric. Preferably, the support is in the form of a nonwoven fabric, woven fabric, or mesh, more preferably, in the form of a nonwoven fabric or mesh, and even more preferably, in the form of a nonwoven fabric.
[0064] The porous support is preferably a nonwoven fabric, a woven fabric, or a mesh containing at least one resin selected from the group consisting of polypropylene, polyethylene, and polyphenylene sulfide.Furthermore, the porous support is preferably a nonwoven fabric or a mesh containing polyphenylene sulfide.
[0065] When the porous support is in the form of a sheet, the thickness of the porous support is not particularly limited as long as the diaphragm for alkaline water electrolysis of the present invention can exhibit the effects of the present invention; however, the thickness is, for example, preferably 30 to 2000 μm, more preferably 50 to 1000 μm, even more preferably 80 to 500 μm, and most preferably 80 to 250 μm.
[0066] The thickness of the porous support can be determined from a microscopic image obtained by observing a cross section of the diaphragm for alkaline water electrolysis of the present invention cut in the thickness direction, i.e., in the direction perpendicular to the surface of the diaphragm, with a field emission scanning electron microscope (FE-SEM). Usually, the thickness is measured at any multiple positions, for example, five positions, and the average value of the measurements can be used as the thickness of the porous support.
[0067] Furthermore, when the porous support can be isolated, the thickness can be measured using a commercially available measuring device, as in the case of the thickness of the diaphragm for alkaline water electrolysis of the present invention. For example, a value measured using a Digimatic Micrometer (manufactured by Mitutoyo Corporation) can be used. Measurements are taken at any 5 or more points (for example, 10 points), and the average value can be used as the thickness of the porous support.
[0068] The air permeability of the separator for alkaline water electrolysis of the present invention is not particularly limited, but is preferably 50 to 5000 seconds. An air permeability in the above-mentioned range provides good gas barrier properties and effectively prevents mixing of oxygen gas and hydrogen gas. The air permeability is preferably 100 to 1000 seconds, and more preferably 150 to 800 seconds. The air permeability can be determined by the measurement method described above using air as the measurement gas.
[0069] The thickness of the diaphragm for alkaline water electrolysis of the present invention is not particularly limited and may be appropriately selected depending on the size and handleability of the equipment used, but is preferably 50 to 2000 μm, more preferably 100 to 1000 μm, further preferably 100 to 500 μm, and most preferably 150 to 350 μm. The method for measuring the thickness is not particularly limited, but it is preferable to use a value measured with a micrometer, for example. Usually, it is preferable to measure at multiple locations, for example 10 locations, and to use the average value as the thickness of the diaphragm. As the micrometer, it is preferable to use a commercially available product, for example a Digimatic Micrometer (manufactured by Mitutoyo Corporation).
[0070] The diaphragm for alkaline water electrolysis of the present invention has a porosity of preferably 25 to 80%, more preferably 30 to 75%, and even more preferably 35 to 70%. When the porosity of the entire membrane is within the above range, the voids in the diaphragm are more continuously filled with the electrolytic solution, and the membrane is likely to exhibit higher ion conductivity. The porosity can be calculated from the following formula using the actual density value of the diaphragm measured by the method described below and the calculated density value of the diaphragm calculated using the density values (true density) and composition ratios of each component constituting the diaphragm. Porosity (%) = [1-(actual density value) / (calculated density value)] x 100 The actual density value can be calculated by measuring the mass and volume of a test piece cut out from any location of the obtained membrane, and dividing the mass by the volume. The volume can be calculated by measuring the vertical and horizontal lengths of the test piece using calipers, and measuring the film thickness according to the film thickness measurement method described above. The mass of the test piece can be measured using a precision balance with four decimal places for the test piece whose volume has been measured.
[0071] The ionic conductivity of the diaphragm for alkaline water electrolysis of the present invention can be calculated by the method described in the Examples. The ionic conductivity of the diaphragm for alkaline water electrolysis of the present invention is preferably more than 100 mS / cm. In this case, the electrolysis efficiency in alkaline water electrolysis can be further increased.
[0072] The diaphragm for alkaline water electrolysis of the present invention preferably has a mass loss rate due to falling off of diaphragm components after ultrasonic treatment in water at 30°C at a frequency of 38 kHz and an output of 100 W for 3 minutes of 2% or less. Subjecting the diaphragm to ultrasonic treatment may cause some of the diaphragm components to fall off. If the diaphragm has low strength, the diaphragm components are more likely to fall off due to ultrasonic treatment, and the amount that falls off increases. The mass loss rate due to falling off of diaphragm components is more preferably 1.5% or less, further preferably 1.2% or less, and particularly preferably 1% or less.
[0073] The mass loss rate of the above-mentioned diaphragm for alkaline water electrolysis due to dropout of diaphragm components before and after ultrasonic treatment in water at 30°C at a frequency of 38 kHz and an output of 100 W for 3 minutes can be calculated according to the following formula. Mass reduction rate (%) = 100 - (membrane mass after ultrasonic treatment) / (membrane mass before ultrasonic treatment) x 100 In the ultrasonic treatment test, the diaphragm is placed so that the entire diaphragm is immersed in water.
[0074] The diaphragm for alkaline water electrolysis of the present invention preferably has a membrane resistance ratio calculated by the following formula when subjected to the hot alkaline durability test described below, of 0.7 or more, and more preferably 0.8 or more. Membrane resistance ratio = (membrane resistance after 240 hours) / (membrane resistance after 24 hours) (Hot alkali durability test) The diaphragm for alkaline water electrolysis of the present invention was cut into a 3 cm square to prepare a test piece. Two test pieces were placed in a fluororesin container (made of PFA) and immersed in 30 g of a 30% KOH aqueous solution and maintained at 90°C. After 24 and 240 hours of immersion, the test pieces were removed and the membrane resistance was measured at room temperature. The membrane resistance can be measured by the method described in the Examples.
[0075] The diaphragm for alkaline water electrolysis of the present invention has the above-mentioned configuration and therefore exhibits excellent stability of ion conductivity in hot alkaline water. Therefore, by using the diaphragm for alkaline water electrolysis of the present invention as a diaphragm in a water electrolysis apparatus using an alkaline aqueous solution as the electrolyte, high-purity hydrogen gas can be produced stably for a long period of time.
[0076] The method for producing the diaphragm for alkaline water electrolysis of the present invention is not particularly limited, and preferred methods include, for example, the production method (1) (embodiment 3) or the production method (2) (embodiment 4) described below.
[0077] 2. Composition for diaphragms in alkaline water electrolysis A composition for a diaphragm for alkaline water electrolysis, which is a preferred embodiment (embodiment 2) of the present invention, will be described below. The composition according to embodiment 2 is also referred to as composition (i) of the present invention or simply as composition (i).
[0078] The composition (i) contains an organic polymer and inorganic particles, and is mixed at a shear rate of 10 s -1 The viscosity at 25°C is 30,000 mPa s or less and the shear rate is 0.1 s -1 The composition has a viscosity (25°C) of 100,000 mPa s or more for use in a diaphragm for alkaline water electrolysis.
[0079] Viscosity (25°C) is the viscosity at room temperature (25°C) and is measured by the following method. (Method of measuring viscosity (25℃)) Using a rheometer (HAAKE Rheost 6000) and a plate PP35Ti (D = 35 mm), the sample is left in a 25°C atmosphere for 2 hours, and the sample stage is adjusted to 25°C and then an appropriate amount is placed in the sample. Shear rate: 500 s -1 The sample was homogenized by treating with 0 for 30 seconds, then held for 10 seconds without shearing to adjust the temperature, and then subjected to a shear rate of 0 to 300 s -1 1000 measurement points are acquired in 9 minutes. -1 , 10s -1 , 250s -1 For each of the measurements, a linear approximation was calculated at five points before and after the nearest measurement point, and the calculated values were used for each shear rate (0.1 s -1 , 10s -1 , 250s -1 ) is the viscosity (25°C) value.
[0080] Composition (i) can be preferably used as a composition for producing a diaphragm for alkaline water electrolysis, in particular as a coating composition, and can also be preferably used as a composition for producing a diaphragm for alkaline water electrolysis described as Embodiment 1 of the present invention. Note that preferred aspects of composition (i) described below are also preferred aspects when used as a coating composition.
[0081] Composition (i) is mixed at a shear rate of 10 s -1 The viscosity (25°C) is 30,000 mPa·s or less at a shear rate of 10 s -1 The viscosity at 25° C. is preferably 25,000 mPa·s or less, and more preferably 20,000 mPa·s or less.
[0082] When the composition (i) is used as a coating composition, it is preferable that the composition (i) is applied at a shear rate of 10 s -1 Since the viscosity at 25°C is low, the composition has excellent coating performance when applied, and is useful as a composition that exhibits effects such as easy control of the amount applied (coating thickness) and excellent impregnation when applied to a porous support.
[0083] The composition (i) is mixed at a shear rate of 10 s -1 It is preferable that the viscosity (25°C) at a shear rate of 10 s is 10,000 mPa·s or more. If it is less than 10,000 mPa·s, the fluidity may be too high and the yield at the time of application may decrease. -1 The viscosity at 25° C. is more preferably 12000 mPa·s or more, and further preferably 14000 mPa·s or more.
[0084] The composition (i) is heated at a shear rate of 250 s -1 The viscosity (25°C) of the composition (i) is preferably 15000 mPa·s or less, more preferably 12000 mPa·s or less, and even more preferably 10000 mPa·s or less at a shear rate of 250 s -1 It is preferable that the viscosity (25°C) at a shear rate of 250 s is 5000 mPa·s or more. -1 The viscosity at 25° C. is more preferably 6000 mPa·s or more, and further preferably 7000 mPa·s or more.
[0085] The composition (i) is mixed at a shear rate of 0.1 s -1 The viscosity (25°C) is 100,000 mPa·s or more at a shear rate of 0.1 s -1The viscosity (25°C) at a shear rate of 0.1 s is preferably 200,000 mPa·s or more, and more preferably 300,000 mPa·s or more. -1 Since the viscosity at 25° C. is 100,000 mPa·s or more, the composition (i) is useful as a composition for obtaining a film in which the generation and growth of macrovoids is suppressed. The composition (i) is mixed at a shear rate of 0.1 s -1 The viscosity at 25° C. is preferably 600,000 mPa·s or less, more preferably 500,000 Pa·s or less, and further preferably 450,000 Pa·s or less.
[0086] In the above composition (i), the shear rate is 0.1 s -1 Viscosity (25°C) at A and shear rate of 10 s -1 When the viscosity (25°C) at is taken as B, the ratio of A to B (A / B) is preferably 5 or more. The ratio (A / B) is more preferably 8 or more, further preferably 15 or more, and particularly preferably 20 or more. On the other hand, the upper limit is not particularly limited, but is usually 60 or less, preferably 50 or less, and more preferably 40 or less.
[0087] The composition (i) contains an organic polymer. The organic polymer can be the same as the organic polymer contained in the porous layer constituting the diaphragm for alkaline water electrolysis of the present invention, and preferred embodiments thereof are also the same. The composition (i) contains inorganic particles. The inorganic particles can be the same as the inorganic particles contained in the porous layer constituting the diaphragm for alkaline water electrolysis of the present invention, and preferred aspects thereof are also the same.
[0088] The composition (i) preferably further contains a solvent. The solvent is not particularly limited, but is preferably an organic solvent, and is preferably one capable of dissolving an organic polymer. Preferred organic solvents include, for example, organic solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, and dimethylsulfoxide. These solvents may be used alone or in combination of two or more. Among them, N-methyl-2-pyrrolidone is preferred because it has excellent solubility for organic polymers and excellent dispersibility for inorganic particles. The solvent may contain other organic solvents than water, etc.
[0089] The composition (i) may also contain a metal chloride. Examples of the metal chloride include lithium chloride, sodium chloride, potassium chloride, magnesium chloride, calcium chloride, and the like. These salts may be used alone or in combination of two or more. Among them, lithium chloride is preferred because of its excellent solubility in a solvent. By including a metal chloride, it becomes easier to control the viscosity of the composition (i) to the above-mentioned preferred range. The content of the metal chloride is preferably 0.001% by mass or more and less than 1% by mass relative to 100% by mass of the inorganic particles included in the composition (i). The content of the metal chloride is more preferably 0.01% by mass or more, even more preferably 0.05% by mass or more, and even more preferably 0.5% by mass or less, and even more preferably 0.2% by mass or less, relative to 100% by mass of the inorganic particles. The embodiment in which the composition (i) includes a metal chloride is also one of the preferred embodiments of the present invention. The composition (i) may contain additives other than those described above. For example, a plasticizer, a surfactant, etc. When the composition (i) does not contain a solvent, it is preferable that the composition (i) contains a plasticizer.
[0090] The content, composition ratio, etc. of each component of the composition (i) is not particularly limited so long as it has the above-mentioned viscosity (25° C.) characteristics. For example, the composition (i) contains a solvent, and the total content of the inorganic particles and the organic polymer in the composition (i) is preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 48% by mass or more, relative to 100% by mass of the composition (i). On the other hand, the upper limit is not particularly limited, but is preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less, and particularly preferably 55% by mass or less.
[0091] The content of the inorganic particles in the composition (i) is preferably 50 to 90% by mass relative to 100% by mass of the total content of the inorganic particles and the organic polymer, more preferably 85% by mass or less, even more preferably 80% by mass or less, more preferably 55% by mass or more, and even more preferably 60% by mass or more.
[0092] The content of the metal chloride in the composition (i) is preferably 0.001% by mass or more and less than 1% by mass relative to 100% by mass of the inorganic particles, and more preferably within the above-mentioned preferred range.
[0093] When the composition (i) does not contain a solvent, the total content of the organic polymer and the inorganic particles is preferably 80 to 100% by mass relative to 100% by mass of the composition (i). When the content is within the above range, it becomes easy to control the viscosity of the composition (i) to the above preferred range.
[0094] As described above, composition (i) contains an organic polymer and inorganic particles, and has a high viscosity (25°C) of a predetermined value or more at a low shear rate, while having a relatively low viscosity (25°C) at a high shear rate. This is not only advantageous for controlling the structure of the membrane, such as by suppressing the generation and growth of macrovoids, but also provides excellent coating performance, such as controllability of the coating amount (coating thickness) and impregnation, and therefore can be preferably used, for example, as a coating composition for producing alkaline water electrolysis having excellent stability of ion conductivity in hot alkali.
[0095] Furthermore, the effect of inhibiting the formation and growth of macrovoids due to the viscosity characteristics of composition (i) becomes more pronounced when a coating film obtained using composition (i) is subjected to a reaction (solidification reaction) utilizing a non-solvent induced phase separation method. Thus, composition (i) can be particularly preferably used as a coating composition in a production method for a diaphragm for alkaline water electrolysis that includes a non-solvent induced phase separation step.
[0096] In addition, when the composition (i) is used as a coating composition, the composition (i) preferably contains a solvent. By containing a solvent, the composition (i) has better coating performance and is easy to control the porous structure when a coating film obtained by using the composition (i) is subjected to a non-solvent induced phase separation process.
[0097] The composition (i) can also be preferably used as a molding composition for producing a diaphragm for alkaline water electrolysis, in particular in a method for producing a diaphragm for alkaline water electrolysis in which a thermally induced phase separation method is applied to a membrane obtained by molding. When the above composition (i) is used as a molding composition, it is preferable that the composition does not contain a solvent.
[0098] The method for preparing the composition (i) is not particularly limited, and the composition (i) can be prepared by mixing an organic polymer and inorganic particles. The above-mentioned mixing method is not particularly limited, and a conventionally known mixing and dispersing method can be adopted. For example, known mixing and dispersing means such as a melt kneading method, a mixer, a ball mill, a jet mill, a disperser, a sand mill, a roll mill, a pot mill, a paint shaker, etc. can be mentioned. In addition, a dispersant, etc. may be appropriately added as necessary.
[0099] It is preferable to use a solvent because it is easy to mix the organic polymer and the inorganic particles uniformly.As a method for preparing a mixture using a solvent, for example, when mixing an organic polymer, an inorganic particle, and a solvent, the three components may be mixed simultaneously, or a dispersion liquid in which inorganic particles are dispersed in a solvent may be prepared in advance, and then the dispersion liquid and the organic polymer may be mixed, or a dispersion liquid in which inorganic particles are dispersed and a resin liquid in which an organic polymer is dispersed or dissolved in a solvent may be prepared in advance, and then these dispersion liquids and the resin liquid may be mixed.As the solvent, the same solvent as the above solvent can be used, and the preferred embodiment is also the same.
[0100] Among them, a method of preparing a dispersion liquid in which inorganic particles are dispersed and a resin liquid in which an organic polymer is dispersed or dissolved in a solvent in advance, and then mixing these dispersion liquids and the resin liquid is preferred, because it is easy to control the dispersion state of the inorganic particles and allows the organic polymer and the inorganic particles to be mixed uniformly. The organic polymer and inorganic particles used here are the same as the organic polymer and inorganic particles described in the second embodiment, respectively.
[0101] The concentration of the inorganic particles in the dispersion is not particularly limited, but is preferably 30 to 60% by mass relative to 100% by mass of the dispersion in terms of ease of mixing. More preferably, it is 40 to 60% by mass, and even more preferably, it is 50 to 60% by mass. Even when the dispersion further contains a metal chloride, the concentration of the inorganic particles in the dispersion is the same as above.
[0102] The concentration of the organic polymer in the resin liquid in which the organic polymer is dispersed or dissolved is not particularly limited, but is preferably 10 to 50% by mass relative to 100% by mass of the resin liquid in terms of ease of mixing, more preferably 20 to 40% by mass, and even more preferably 25 to 35% by mass. Even when the resin liquid further contains a metal chloride, the concentration of the organic polymer in the resin liquid is the same as above.
[0103] The method of mixing or dispersing is not particularly limited, and examples thereof include known mixing and dispersing means such as a method using a mixer, a ball mill, a jet mill, a disperser, a sand mill, a roll mill, a pot mill, a paint shaker, etc. A dispersant, etc. may also be added as appropriate.
[0104] The mixture containing inorganic particles, organic polymer and solvent obtained as described above can be used as composition (i), and further, a mixture containing additives such as metal chloride can also be used as composition (i). For example, the method of mixing additives is not particularly limited. When mixing metal chloride, for example, the metal chloride may be added to the mixture obtained by the above method, or the metal chloride may be mixed when preparing a dispersion liquid in which inorganic particles are dispersed in a solvent, or may be added to a dispersion liquid in which inorganic particles are dispersed in a solvent, or may be added to a resin liquid in which an organic polymer is dissolved or dispersed. The same applies when additives other than metal chloride are mixed.
[0105] As a method for adding the metal chloride, a method of adding the metal chloride to a dispersion liquid in which inorganic particles are dispersed in a solvent, a method of adding the metal chloride to a mixture containing inorganic particles, an organic polymer, and a solvent, and the like are preferred, in that thickening and the like is unlikely to occur during the preparation of the above composition (i) and a uniform mixture of the components can be easily obtained.
[0106] When the metal chloride is mixed with the dispersion liquid, the metal chloride may be mixed in powder form, or a liquid (additive liquid) in which the metal chloride is dissolved or dispersed in a solvent may be prepared in advance and used. As the solvent, the same solvent as that mixed with the organic polymer or inorganic particles may be preferably used.
[0107] When the above composition (i) contains a solvent, a preparation method using the above solvent is adopted, and the type of organic polymer (material, molecular weight), the type of inorganic particle (material, shape, particle size), the type of solvent (solubility, polarity), the content of each of these, their combination, the presence or absence of addition of additives such as metal chlorides, and the amount thereof are appropriately selected to adjust the viscosity characteristics, thereby obtaining composition (i) according to embodiment 2 of the present invention.
[0108] 3. Manufacturing method of diaphragm for alkaline water electrolysis The method for producing the diaphragm for alkaline water electrolysis of the present invention will be described. Methods for producing a diaphragm for alkaline water electrolysis according to the present invention are the following production methods (1) and (2). The above-mentioned production method (1) includes an organic polymer and an inorganic particle, and is subjected to a shear rate of 10 s -1 The viscosity at 25°C is 30,000 mPa s or less, and the shear rate is 0.1 s -1 The present invention is characterized in that it uses a composition having a viscosity (25°C) of 100,000 mPa·s or more. The above-mentioned production method (2) includes an organic polymer and an inorganic particle, and is heated at a shear rate of 0.1 s -1 The method is characterized in that it includes a step of using a composition having a viscosity (25°C) of 100,000 mPa·s or more and applying the composition at a shear rate such that the viscosity of the composition is 30,000 mPa·s or less. The use of the production method (1) or (2) makes it possible to efficiently produce the diaphragm for alkaline water electrolysis of the present invention (Embodiment 1). Furthermore, the use of the production method (1) or (2) makes it possible to efficiently produce a diaphragm for alkaline water electrolysis having excellent stability of ion conductivity in hot alkali.
[0109] <Manufacturing method of diaphragm for alkaline water electrolysis (1)> A method (1) for producing a diaphragm for alkaline water electrolysis, which is a preferred embodiment (embodiment 3) of the present invention, will be described. The composition used in the above production method (1) is also referred to as composition (A). As the composition (A), the same composition as the above composition (i) can be used, and the preferred embodiments thereof are also the same as those of the above composition (i).
[0110] The above-mentioned production method (1) is preferably a method in which a membrane is formed using the above-mentioned composition (A), and the obtained membrane is subjected to phase separation to produce a membrane having a porous structure. Among them, a production method including the following steps (1a) to (3a) is preferable. (1a) Step of preparing composition (A) (2a) Step of forming a coating film using composition (A) (3a) forming a porous structure on the coating film by a non-solvent induced phase separation method; As a method for preparing the composition (A) in the step (1a), the preparation method for the composition (i) explained in the embodiment 2 can be directly adopted. The same applies to the preferred embodiment. The step (1a) is preferably a step for preparing a composition (coating composition) containing a solvent. Step (2a) is a step of forming a coating film using the composition (A) obtained in the above step (1a).
[0111] It is preferable to use a composition containing a solvent (coating composition) as the composition (A). When the composition (A) is used as a coating composition, it is preferably applied at a shear rate of 10 s -1 Since the viscosity at 25°C is low, the fluidity during application is excellent, resulting in excellent coating performance. Therefore, the composition (A) can be used, for example, as a coating composition which is easy to control uniformly in coating amount (coating thickness) and has excellent impregnation properties for a porous support. The preferred embodiment of the composition (A) when used as a coating composition in the production method (2) is the same as the preferred embodiment of the composition (i) described above.
[0112] A preferred method for forming the coating film is, for example, a method of applying the composition (A) onto a substrate, etc. The step (2a) preferably includes a step of applying the composition (A) onto a porous support. The coating method is not particularly limited, and examples thereof include known coating means such as die coating, spin coating, gravure coating, curtain coating, spraying, and methods using an applicator or coater.
[0113] The substrate is not particularly limited as long as it can be coated with the composition (A) to form a coating film, and examples thereof include, in addition to a porous support, films or sheets made of resins such as polytetraethylene terephthalate, polyethylene naphthalate, polypropylene, polyethylene, polyvinyl chloride, polyvinyl acetal, polymethyl methacrylate, polycarbonate, etc., glass plates, etc. Among these, polytetraethylene terephthalate films or sheets are preferred. As the porous support, the same one as described above in the description of the first embodiment can be used, and the preferred aspects are also the same.
[0114] When the diaphragm for alkaline water electrolysis includes a porous support, the composition (A) may be applied to the porous support. Examples of the application method include a method in which the composition (A) is directly applied to the porous support, and a method in which the porous support is immersed in the composition (A). Examples of the application method include a method in which the composition (A) is applied to the above-mentioned substrate, and the porous support is brought into contact with the applied product to impregnate the porous support with the composition (A). By impregnating the porous support with the composition (A), a composite in which a coating film derived from the composition (A) and the porous support are integrated can be produced. The amount of the composition (A) to be applied is not particularly limited, and may be appropriately determined so that the resulting membrane has a thickness that allows the above-mentioned effects to be exhibited.
[0115] The above step (3a) is a step of forming a porous structure from the coating film obtained in step (2a) by a non-solvent-induced phase separation method. Step (3a) can also be said to be a step of forming a porous structure from the coating film obtained in step (2a) by contacting the coating film with a liquid containing a non-solvent for the organic polymer. The liquid containing a non-solvent for the organic polymer is also called a non-solvent-containing liquid. By contacting the coating with a liquid containing a non-solvent for the organic polymer, the non-solvent diffuses into the coating, and the organic polymer that is not soluble in the non-solvent solidifies. Meanwhile, the solvent in the coating that is soluble in the non-solvent dissolves from the coating. Such phase separation causes the organic polymer to solidify, forming a porous structure.
[0116] The composition (A) for forming the coating film is heated at a shear rate of 0.1 s -1 When the viscosity (25°C) is 100,000 mPa s or more, the phase separation rate of a coating film made of the composition is suppressed, making it easier to obtain a porous structure in which the generation and growth of macrovoids is suppressed.
[0117] The method of contacting the coating film with the non-solvent-containing liquid includes a method of immersing the coating film in the non-solvent-containing liquid (coagulation bath), etc. When the composition (A) for forming a porous layer is applied to a porous support to form a coating film, the porous support on which the coating film has been formed may be immersed in the non-solvent.
[0118] The non-solvent for the organic polymer may be a solvent that does not substantially dissolve the organic polymer, where the solubility of the organic polymer in 100 g of the solvent at 25° C. is 100 mg or less. Examples of the non-solvent include water, such as pure water, distilled water, and ion-exchanged water; lower alcohols, such as methanol, ethanol, and propyl alcohol; and mixed solvents thereof. Among these, water is preferred from the viewpoints of economy and wastewater treatment, and ion-exchanged water is more preferred. The non-solvent-containing liquid may contain a non-solvent for the organic polymer, and its concentration is not particularly limited. For example, one preferred embodiment is one in which the concentration of the non-solvent in the non-solvent-containing liquid is 100% by mass or is maintained at a concentration close to 100% by mass.
[0119] On the other hand, a preferred embodiment is one in which the non-solvent-containing liquid contains a solvent other than the non-solvent. In this case, the concentration of the non-solvent in the non-solvent-containing liquid is preferably 10% by mass or more. More preferably, it is 20% by mass or more, and even more preferably, it is 40% by mass or more. On the other hand, the upper limit is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably, it is 60% by mass or less.
[0120] The non-solvent-containing liquid preferably contains the non-solvent in a proportion of 10% by mass or more and 90% by mass or less, more preferably 20% by mass or more, and even more preferably 40% by mass or more, relative to 100% by mass of the total amount of the non-solvent and the solvent other than the non-solvent contained in the non-solvent-containing liquid, while the upper limit is more preferably 80% by mass or less, and even more preferably 60% by mass or less.
[0121] In addition, the solvent other than the non-solvent is not particularly limited, but preferably contains the same solvent as the solvent contained in the coating film. When the non-solvent-containing liquid contains the same solvent as the solvent contained in the coating film, the content of the same solvent as the solvent contained in the coating film is preferably 10% by mass or more and 90% by mass or less, more preferably 20% by mass or more and 80% by mass or less, and even more preferably 40% by mass or more and 60% by mass or less, based on 100% by mass of the total amount of the non-solvent and the solvent other than the non-solvent contained in the non-solvent-containing liquid.
[0122] The temperature condition in the above step (3a) is preferably 5 to 30°C, more preferably 10 to 30°C, and even more preferably 15 to 30°C, in order to enable the coating to be solidified uniformly. By the above step (3a), the coating film formed in the above step (2a) is solidified to have a porous structure. The coating film solidified to have a porous structure contains the solvent component contained in the non-solvent-containing liquid used in step (3a) such as the non-solvent and / or the solvent component contained in the coating film formed in step (2a).
[0123] The method (1) for producing a diaphragm for alkaline water electrolysis of the present invention preferably further includes the following step (4a): (4) A step of drying the coating film having a porous structure obtained in step (3a) to obtain a porous layer. In step (4a), a porous layer can be obtained by removing volatile components such as non-solvent contained in the coating film having a porous structure obtained in step (3a).
[0124] The drying temperature is preferably 60 to 100° C., more preferably 60 to 80° C. The drying time is preferably 2 to 60 minutes, more preferably 2 to 30 minutes, and even more preferably 5 to 30 minutes.
[0125] The method (1) for producing a diaphragm for alkaline water electrolysis may include other known steps, such as a pressing step for making the density of the diaphragm uniform, in addition to the above-described steps (1a) to (4). As described above, the method (1) for producing a diaphragm for alkaline water electrolysis of the present invention is preferably a method including the above steps (1a) to (3a), and more preferably a method including steps (1a) to (4a). However, the method (1) for producing a diaphragm for alkaline water electrolysis of the present invention is not limited to these preferred embodiments.
[0126] <Manufacturing method of diaphragm for alkaline water electrolysis (2)> A production method (2) of a diaphragm for alkaline water electrolysis, which is a preferred embodiment (embodiment 4) of the present invention, will be described. The above-mentioned production method (2) includes an organic polymer and an inorganic particle, and is heated at a shear rate of 0.1 s -1 The method is characterized in that it includes a step of using a composition having a viscosity (25°C) of 100,000 mPa·s or more and applying the composition at a shear rate such that the viscosity of the composition is 30,000 mPa·s or less. The composition used in the above production method (2) is referred to as composition (B).
[0127] The composition (B) contains an organic polymer and inorganic particles, and is heated at a shear rate of 0.1 s -1 The viscosity at 25°C is 100,000 mPa s or more. The organic polymer and inorganic particles are the same as those used in the production method (1), and preferred embodiments thereof are also the same.
[0128] The composition (B) is heated at a shear rate of 0.1 s -1 The viscosity (25°C) is 100,000 mPa·s or more at a shear rate of 0.1 s -1 The viscosity at 25° C. is preferably 200,000 mPa·s or more, and more preferably 300,000 mPa·s or more. The composition (B) is heated at a shear rate of 0.1 s -1 The viscosity at 25° C. is preferably 600,000 mPa·s or less, more preferably 500,000 Pa·s or less, and further preferably 450,000 Pa·s or less.
[0129] The composition (B) is heated at a shear rate of 10 s -1 The viscosity (25°C) is preferably 30,000 mPa·s or less, more preferably 25,000 mPa·s or less, and even more preferably 20,000 mPa·s or less, while the lower limit is preferably 10,000 mPa·s or more, and more preferably 12,000 mPa·s or more.
[0130] The composition (B) was heated at a shear rate of 250 s -1 The viscosity (25°C) at a shear rate of 250 s is preferably 15,000 mPa·s or less, more preferably 12,000 mPa·s or less, and even more preferably 10,000 mPa·s or less. -1 The viscosity at 25° C. is preferably 5000 mPa·s or more, more preferably 6000 mPa·s or more, and even more preferably 7000 mPa·s or more.
[0131] The composition (B) preferably further contains a solvent. The solvent is not particularly limited, but is preferably an organic solvent, and is preferably one that can dissolve an organic polymer. The preferred organic solvent is the same as the solvent that can be used in the composition (i).
[0132] The composition (B) preferably contains a metal chloride, and the preferred types of metal chlorides, the preferred content of metal chlorides, etc. are the same as those of the metal chlorides in the composition (i). The composition (B) may contain additives other than those mentioned above. The preferred embodiments thereof are the same as those of the composition (i). As long as the composition (B) has the above-mentioned viscosity (25° C.) characteristics, there are no particular limitations on the contents and composition ratios of the respective components.
[0133] For example, the composition (B) contains a solvent, and the total content of the inorganic particles and the organic polymer in the composition (B) is preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 48% by mass or more, relative to 100% by mass of the composition (B). On the other hand, the upper limit is not particularly limited, but is preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less, and particularly preferably 55% by mass or less.
[0134] The content of the inorganic particles in the composition (B) is preferably 50 to 90% by mass relative to 100% by mass of the total content of the inorganic particles and the organic polymer, more preferably 85% by mass or less, even more preferably 80% by mass or less, more preferably 55% by mass or more, and even more preferably 60% by mass or more.
[0135] When composition (B) contains the metal chloride, the content of the metal chloride contained in composition (B) is preferably 0.001% by mass or more and less than 1% by mass relative to 100% by mass of the inorganic particles. The content of the metal chloride is more preferably 0.01% by mass or more, even more preferably 0.05% by mass or more, and more preferably 0.5% by mass or less, even more preferably 0.2% by mass or less, relative to 100% by mass of the inorganic particles. The composition (B) can be prepared in the same manner as the preparation method of the composition (i) explained in the second embodiment.
[0136] The above-mentioned production method (2) is not particularly limited as long as it includes a step of using the above-mentioned composition (B) and applying the composition at a shear rate that gives the composition a viscosity of 30,000 mPa s or less. However, it is preferable that the production method includes the following steps (1b) to (3b): (1b) Step of preparing composition (B) (2b) Step of forming a coating film using composition (B) (3b) forming a porous structure on the coating film by a non-solvent induced phase separation method; In step (1b), composition (B) can be prepared by applying the preparation method of composition (i) explained in embodiment 2, i.e., the preparation method of composition (A) in step (1a) mutatis mutandis. Step (1b) is preferably a step of preparing a composition (coating composition) containing a solvent as composition (B). Step (2b) is a step of forming a coating film using the composition (B) obtained in the above step (1b). As the composition (B), it is preferable to use a composition containing a solvent (a coating composition). In step (2b), it is necessary to apply composition (B) at a shear rate at which the viscosity of composition (B) becomes 30,000 mPa·s or less.
[0137] The shear rate means the maximum shear rate applied to the composition (B) during coating. The maximum shear rate will be explained using FIG. 1 as an example. FIG. 1 is a schematic diagram showing the configuration of a coater viewed from the side. The shear rate is determined by V / H, where V (m / s) is the transport speed of the substrate and H (m). As shown in FIG. 1, the coating liquid such as the composition (B) is introduced near the coater and sandwiched between the coater and the back roll, and is subjected to shear corresponding to the distance between the coater and the back roll, that is, the gap H. The gap H gradually becomes smaller toward the tip of the coater and is minimum at the tip of the blade. When the speed is constant, the shear rate applied to the coating liquid is maximum at the position where the gap H is minimum. This shear rate is the maximum shear rate, and in the case of a coater, it is the shear rate applied to the coating liquid at the tip of the blade.
[0138] In other words, in step (2b), it is necessary to control the maximum shear rate so that the viscosity of composition (B) during application is 30,000 mPa·s or less. By controlling the viscosity during coating within the above range, coating can be performed with excellent uniformity in coating thickness and excellent impregnation into the porous support.
[0139] The maximum shear rate is preferably adjusted so that the viscosity of composition (B) during application is 30,000 mPa·s or less, more preferably 25,000 mPa·s or less, and even more preferably 20,000 mPa·s or less. On the other hand, the upper limit of the viscosity is preferably 5,000 mPa·s or more, more preferably 6,000 mPa·s or more.
[0140] The temperature of the composition (B) during application is not particularly limited, but is preferably from 0 to 50°C, more preferably from 10 to 40°C, and even more preferably from 15 to 35°C.
[0141] A preferred method for forming the coating film is, for example, a method of applying the composition (B) onto a substrate, etc. The step (2a) preferably includes a step of applying the composition (B) onto a porous support.
[0142] The coating method is not particularly limited, and examples thereof include known coating means such as die coating, spin coating, gravure coating, curtain coating, spraying, and methods using an applicator or coater, etc. Among these, coating methods using die coating, coaters, etc. are preferred because it is easy to adjust the maximum shear rate so that the viscosity of composition (B) during coating is 30,000 mPa s or less in the above-mentioned preferred temperature range.
[0143] The above substrate and the above porous support are the same as those in step (2a) of the above production method (1), and preferred embodiments are also the same. When a diaphragm for alkaline water electrolysis containing a porous support is produced, it is preferable to apply composition (B) to the porous support, and the application method and preferred aspects are the same as those in step (2a) in production method (1). The application amount of composition (B) is not particularly limited and may be appropriately set so that the obtained diaphragm has a thickness that can exhibit the above-mentioned effects.
[0144] The above step (3b) is a step of forming a porous structure from the coating film obtained in step (2b) by a non-solvent-induced phase separation method. Step (3b) can also be said to be a step of forming a porous structure from the coating film obtained in step (2b) by contacting the coating film obtained in step (2b) with a liquid containing a non-solvent for the organic polymer (non-solvent-containing liquid). In the above step (3b), various conditions such as the type of non-solvent, the composition of the non-solvent-containing liquid, and temperature are the same as those in the step (3a) in the production method (1), including preferred embodiments. In the step (3b), the coating film formed in the step (2b) solidifies and becomes porous.
[0145] The coating film is subjected to a shear rate of 0.1 s -1Since the coating film is obtained by applying composition (B) having a viscosity at 25°C of 100,000 mPa s or more, the phase separation reaction in the coating film proceeds slowly, making it easier to obtain a porous structure in which the generation and growth of macrovoids is suppressed. The coating film with a porous structure contains the solvent component contained in the non-solvent-containing liquid used in step (3b) and / or the solvent component contained in the coating film formed in step (2b).
[0146] The above production method (2) preferably further comprises the following step (4b): (4b) A step of drying the coating film having a porous structure obtained in step (3b) to obtain a porous layer. In the above step (4b), various conditions such as drying temperature, drying time, etc. are the same as those in the step (4a) in the production method (1), including preferred embodiments. The above-mentioned production method (2) may include other known steps, such as a pressing step for making the density of the diaphragm uniform, in addition to the above-mentioned steps (1b) to (4b).
[0147] As described above, the method (2) for producing a diaphragm for alkaline water electrolysis of the present invention is preferably a method including the above steps (1b) to (3b), and more preferably a method including steps (1b) to (4b). However, the method (2) for producing a diaphragm for alkaline water electrolysis of the present invention is not limited to these preferred embodiments.
[0148] 4. Diaphragm for alkaline water electrolysis according to embodiment 5 As a preferred embodiment (embodiment 5) of the present invention, a composition comprising an organic polymer and inorganic particles and a shear rate of 10 s -1 The viscosity at 25°C is 30,000 mPa s or less and the shear rate is 0.1 s -1 Examples of suitable electrolysis membranes include diaphragms for alkaline water electrolysis produced using a composition having a viscosity at 25°C of 100,000 mPa·s or more.
[0149] The diaphragm for alkaline water electrolysis according to Embodiment 5 is produced using the above composition, and preferred aspects of the composition are similar to the preferred aspects of the composition (i) according to Embodiment 2 and also to the preferred aspects of the composition (A) used in the production method (1) according to Embodiment 3. Furthermore, preferred processes and conditions for producing the diaphragm for alkaline water electrolysis according to Embodiment 5 can be directly applied to the preferred processes and conditions for the production method (1) according to Embodiment 3. The diaphragm for alkaline water electrolysis according to the fifth embodiment can be preferably used, for example, as a diaphragm for alkaline water electrolysis having excellent stability of ion conductivity in hot alkali.
[0150] 5. Diaphragm for alkaline water electrolysis according to embodiment 6 As a preferred embodiment (embodiment 6) of the present invention, a composition comprising an organic polymer and inorganic particles and a shear rate of 0.1 s -1 and applying the composition at a shear rate such that the viscosity of the composition is 30,000 mPa s or less.
[0151] The diaphragm for alkaline water electrolysis according to Embodiment 6 is produced using the above composition, and preferred aspects of the composition are similar to the preferred aspects of composition (B) used in the production method (2) according to Embodiment 4. Furthermore, preferred processes and conditions for producing the diaphragm for alkaline water electrolysis according to Embodiment 6 can be directly applied to the preferred processes and conditions for the production method (2) according to Embodiment 4. The diaphragm for alkaline water electrolysis according to the sixth embodiment can be preferably used, for example, as a diaphragm for alkaline water electrolysis having excellent stability of ion conductivity in hot alkali.
[0152] 6.Applications Any of the diaphragms for alkaline water electrolysis according to the above-mentioned embodiments of the present invention can be suitably used as diaphragms for water electrolysis using an alkaline aqueous solution as an electrolyte solution. The same applies to the diaphragms for alkaline water electrolysis produced by the production method (1) according to embodiment 3 and the production method (2) according to embodiment 4 of the present invention.
[0153] An electrolysis apparatus and an electrolysis method using these diaphragms for alkaline water electrolysis of the present invention are described below. The electrolysis apparatus and electrolysis method described below are not limited to the case where the diaphragm for alkaline water electrolysis according to embodiment 1 is used, but can be directly applied to the case where the diaphragm for alkaline water electrolysis according to embodiment 5 or 6 is used, or to the case where the diaphragm for alkaline water electrolysis produced by the production method according to embodiment 3 or 4 is used.
[0154] (electrolyzer) The diaphragm for alkaline water electrolysis of the present invention is used as a component of an alkaline water electrolysis apparatus. The alkaline water electrolysis apparatus may, for example, include an anode, a cathode, and the diaphragm for alkaline water electrolysis disposed between the anode and the cathode. More specifically, the alkaline water electrolysis apparatus has an electrolytic cell including an anode chamber in which the anode is present, and a cathode chamber in which the cathode is present, separated by the diaphragm for alkaline water electrolysis.
[0155] The diaphragm for alkaline water electrolysis is preferably installed so as to be in contact with the anode or the cathode, and more preferably so as to be in contact with the anode and the cathode. A smaller distance between the electrodes reduces the electrical resistance and enables the electrolysis efficiency of the electrolysis device to be increased. The diaphragm for alkaline water electrolysis of the present invention can also be suitably used in an electrolysis device of a so-called "zero gap structure" in which the diaphragm is installed so as to be in contact with each electrode so as to minimize the distance between the electrodes.
[0156] The anode and cathode are not particularly limited as long as they are known electrodes, and examples thereof include electrodes containing a known conductive substrate such as copper, lead, nickel, chromium, titanium, gold, platinum, iron, metal compounds thereof, metal oxides, and alloys containing two or more of these metals. The electrodes may be those in which a catalytic layer is formed on the conductive substrate. The catalytic layer is not particularly limited, and examples thereof include known ones including metal compounds, metal oxides, or alloys containing nickel, cobalt, palladium, iridium, platinum, or the like. The shape of the electrodes is not particularly limited, and examples thereof include known shapes such as a sheet shape, a rod shape, and a prismatic shape. A sheet shape is preferred in that it has a large contact area with the diaphragm for alkaline water electrolysis and can further improve the electrolysis efficiency of the electrolysis device.
[0157] The electrolysis device may further include other commonly used components, such as a gas-liquid separation tank for separating the generated gas from the electrolytic solution, a condenser for stably performing electrolysis, and a mist separator.
[0158] (Electrolysis method) The method for electrolyzing water using an alkaline water electrolysis apparatus comprising the diaphragm for alkaline water electrolysis of the present invention is not particularly limited and can be performed by a known method. For example, water can be electrolyzed by filling an alkaline water electrolysis apparatus comprising the above-mentioned diaphragm for alkaline water electrolysis of the present invention with an electrolytic solution and applying a current in the electrolytic solution.
[0159] The electrolyte is preferably an alkaline aqueous solution in which an electrolyte such as potassium hydroxide or sodium hydroxide is dissolved. The concentration of the electrolyte in the electrolyte is not particularly limited, but is preferably 20 to 40 mass % in order to further increase the electrolysis efficiency.
[0160] The temperature for electrolysis is preferably 50 to 120°C, more preferably 80 to 90°C, in that the ionic conductivity of the electrolyte is improved and the electrolysis efficiency can be further increased. The current application conditions can be performed under known conditions and methods, and are usually 0.2 A / cm2 or more, preferably 0.3 A / cm2 or more. The higher the applied current density, the more hydrogen gas and oxygen gas can be obtained in a short time, and hydrogen can be produced efficiently. The electrolysis voltage is preferably adjusted so that the current density is high, so that it is about 2 V, for example, within a range not exceeding 1.5 to 2.5 V.
[0161] The pressure under which electrolysis is performed is not particularly limited. It may be normal pressure or pressurized pressure. The diaphragm for alkaline water electrolysis of the present invention has excellent abrasion resistance and maintains good gas barrier property, and is therefore useful even when electrolysis is performed under high pressure conditions of 1 MPa or more, such as 3 MPa. EXAMPLES
[0162] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". In the examples, each evaluation was carried out by the following methods.
[0163] <Method for measuring viscosity (25°C) of coating composition> The coating compositions obtained in each Example were subjected to shear rate of 500 s using a rheometer (HAAKE's Rheost 6000) and a plate PP35Ti (D = 35 mm). -1 The sample was homogenized by treating with 0 for 30 seconds, then held for 10 seconds without shearing to adjust the temperature, and then subjected to a shear rate of 0 to 300 s -1 1000 measurement points were acquired in 9 minutes. -1 , 10s -1 , 250s -1 A linear approximation is calculated for each of the five points before and after the nearest measurement point, and the value calculated from them is 0.1s -1 , 10s-1 , 250s -1 The viscosity (25°C) values at each of the above were recorded.
[0164] <How to measure film thickness> The thickness of the diaphragm for alkaline water electrolysis obtained in each Example was measured using a Digimatic Micrometer (manufactured by Mitutoyo Corporation). Measurements were taken at 10 random points, and the average value was regarded as the membrane thickness.
[0165] <Method of measuring macrovoid content> For the diaphragms for alkaline water electrolysis obtained in each Example, etc., observation images of a cross section perpendicular to the diaphragm surface (cross-sectional observation images) were obtained by FE-SEM (manufactured by JEOL Ltd., model number: JSM-7600F) at a magnification of 300x. For the obtained cross-sectional observation image, a range of 60 μm from the outermost surface of the membrane in the depth direction and a range of about 400 μm in the direction perpendicular to the depth direction were set as measurement regions, and image analysis software (Scion Image) was used to extract void images as dark areas and other areas as bright areas. For each extracted void image, the long diameter (Lb) and short diameter (Ls) were obtained, and the individual areas (S) of void images with a long diameter (Lb) of 30 μm or more were obtained, and the sum of these areas was calculated, and the total area obtained was defined as the total area (Sy) of macrovoids. Meanwhile, the area (St) of the above measurement region was calculated, and the ratio (percentage) of (Sy) to (St) (Sy / St×100(%)) was calculated. The same operation was performed for any five fields of view, and the simple average value was defined as the content of macrovoids with a long diameter of 30 μm or more in the measured membrane. The above-mentioned major axis (Lb) and minor axis (Ls) were determined by measuring the thickness direction length (Lt) and the plane direction length (Lf) of each void image, and the larger of (Lt) and (Lf) was designated as the major axis (Lb) and the smaller was designated as the minor axis (Ls). Here, the thickness direction length (Lt) is the length in the thickness direction of the membrane, i.e., the direction perpendicular to the membrane surface, and specifically, the distance between the point in the void image closest to the membrane (porous membrane) surface and the point closest to the opposite surface in the membrane thickness direction (perpendicular to the membrane surface) was defined as the thickness direction length (Lt) of the void. The value obtained by dividing the area (S) of the void by the thickness direction length (Lt) was defined as the planar length (Lf) of the void image.
[0166] <Film resistance> (Measurement method) For the diaphragms for alkaline water electrolysis obtained in each Example, etc., two diaphragm samples for measurement are prepared. Using each diaphragm sample, a cell with the following cell configuration is formed and allowed to stand in a thermostatic bath at 25°C for 30 minutes, after which AC impedance measurement is performed under the following measurement conditions, and the membrane resistance is calculated from the obtained intercept component (Ra) and the intercept component (Rb) when no measurement sample is placed in the cell, and from the following formula. The above measurement is performed on two diaphragm samples, and the average of the obtained measured values (at two points) is calculated, and this is defined as the membrane resistance of the diaphragm. [Membrane resistance (Ωcm 2 )] = (Ra - Rb) x 1.77 (Measurement conditions) Cell configuration Working electrode: Ni plate Counter electrode: Ni plate Electrolyte: 30% by weight potassium hydroxide aqueous solution Sample pretreatment: Immerse in the above electrolyte overnight Effective measurement area: 1.77cm2 AC impedance measurement conditions Applied voltage: 10mV vs. open circuit voltage Frequency range: 100kHz~100Hz <Method of measuring air permeability> The air permeability of the diaphragms for alkaline water electrolysis obtained in each Example was measured using an Oken air permeability tester (manufactured by Asahi Seiko Co., Ltd., model number: EGBO). Measurements were taken at three arbitrary points, and the average value was regarded as the air permeability.
[0167] <Air permeability per unit thickness> For the diaphragms for alkaline water electrolysis obtained in each Example, etc., the air permeability (X) per unit membrane thickness was calculated from the air permeability and membrane thickness determined by the above-mentioned methods according to the following formula: X = membrane air permeability (sec) / membrane thickness (μm) <Hot alkali durability test> The diaphragms for alkaline water electrolysis obtained in each Example were cut into 3 cm squares to prepare test pieces. Two of these test pieces were placed in a fluororesin container (made of PFA) and immersed in 30 g of a 30% KOH aqueous solution at 90°C. The diaphragms were removed after 24 and 240 hours of immersion, and the membrane resistance was measured at room temperature, and (membrane resistance after 240 hours / membrane resistance after 24 hours) was calculated as the membrane resistance ratio after the hot alkali durability test.
[0168] <Evaluation method for ultrasonic testing> For the diaphragms for alkaline water electrolysis obtained in each Example, the mass reduction rate was evaluated by the following ultrasonic test. (Ultrasonic Testing) The diaphragm for alkaline water electrolysis obtained in each Example was cut into a size of 5 × 5 cm to prepare a diaphragm sample. The diaphragm sample and 6 cc of ion exchanged water were placed in a plastic bag with a zipper (Unipack C-4, manufactured by Seisan Nippon Sha), sealed, and left to stand in a water tank for 1 hour and then irradiated with ultrasound for 3 minutes using an ultrasonic cleaner (manufactured by SND Corporation, model name: US-103, high frequency output: 100 W, transmission frequency: 38 kHz) with the water tank temperature adjusted to 30°C. (Mass loss rate after ultrasonic testing) The weight of each diaphragm sample before and after the ultrasonic test was measured using a precision balance (manufactured by A&D Co., Ltd., model number: GH-200), and the mass loss rate was calculated using the following formula. Mass reduction rate (%) = 100 - (mass after ultrasonic test (g) / mass before ultrasonic test (g) x 100) [Example 1] (1. Preparation of Inorganic Particle Dispersion) Magnesium hydroxide (average particle size 0.20 μm, plate-like, aspect ratio 6.21) and N-methyl-2-pyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed in a mass ratio of 1:1, and a magnesium hydroxide dispersion was prepared by dispersing the mixture at room temperature for 6 hours in a pot mill containing zirconia media balls.
[0169] (2. Preparation of Coating Composition) Using the magnesium hydroxide dispersion obtained above, polysulfone resin (manufactured by BASF, product number Ultrason S3010) (PSU) was weighed out so that the solid content was 51% and 40 parts by mass per 100 parts by mass of magnesium hydroxide, and lithium chloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added at 0.1% by mass per 100% by mass of magnesium hydroxide to prepare a mixture. The obtained mixture was mixed at room temperature for about 30 minutes at 1000 rpm in a planetary centrifugal mixer (manufactured by Thinky Corporation, product number Awatori Rentaro ARE-500) to obtain a coating mixture (1). The obtained coating composition (1) was mixed for 10 seconds at 1000 rpm. -1 The viscosity at 25°C is 24,000 mPa s, and at 250 s -1 The viscosity at 25°C is 6000 mPa s, and -1 The viscosity at 25°C was 300,000 mPa s.
[0170] (3. Membrane formation) The coating composition (1) was applied to a polyphenylene sulfide nonwoven fabric (film thickness 130 μm, basis weight 60 g / m2) at a shear rate of 50 s -1 (viscosity at time of application: 17000 mPa s) was applied to the nonwoven fabric to impregnate it. Thereafter, the nonwoven fabric impregnated with the coating composition (1) was bathed in a water tank filled with ion-exchanged water at room temperature for 5 minutes to solidify the coating liquid and form a membrane. After the water bath, the obtained membrane was dried in a dryer at 80°C for 10 minutes to obtain a diaphragm for alkaline water electrolysis (1) consisting of a composite of the nonwoven fabric and a membrane containing magnesium hydroxide and a polysulfone resin. The obtained diaphragm for alkaline water electrolysis (1) was evaluated by the method described above. The membrane thickness was 210 μm. The content of macrovoids with a major axis of 30 μm or more was 15%, and the air permeability per unit membrane thickness was 1.1. The membrane resistance ratio before and after the hot alkali durability test was 0.83, and the mass loss rate after ultrasonic irradiation was 1.1%.
[0171] [Example 2] A coating composition (2) similar to the coating composition (1) was prepared in the same manner as in Example 1. A diaphragm (2) was produced in the same manner as in (3. Formation of film) of Example 1, except that the coating composition (2) was used instead of the coating composition (1), a mixed aqueous solution of 50% ion-exchanged water and 50% N-methyl-2-pyrrolidone was used instead of ion-exchanged water as the non-solvent in the water tank, and the film was left to stand in ion-exchanged water for 10 minutes after solidification. The film thickness of the obtained diaphragm (2) was 195 μm. The content of macrovoids having a major axis of 30 μm or more was 6%, and the air permeability per unit film thickness was 2.0. The film resistance ratio before and after the hot alkali durability test was 0.91, and the mass reduction rate after ultrasonic irradiation was 0.9%.
[0172] [Example 3] In the same manner as in Example 1, a coating composition (3) similar to the coating composition (1) was prepared. A diaphragm (3) was produced in the same manner as in Example 1 (3. Formation of membrane), except that the coating composition (1) was replaced with the coating composition (3), the non-solvent in the water tank was replaced with a mixed aqueous solution of 20% ion-exchanged water and 80% N-methyl-2-pyrrolidone instead of ion-exchanged water, and the membrane was allowed to stand in ion-exchanged water for 10 minutes after solidification. The membrane (3) thus obtained had a thickness of 185 μm. The content of macrovoids having a major axis of 30 μm or more was 3%, and the air permeability per unit membrane thickness was 2.5. The membrane resistance ratio before and after the hot alkali durability test was 0.89, and the mass loss rate after ultrasonic irradiation was 1.3%.
[0173] [Example 4] In the same manner as in Example 1, a coating composition (4) similar to the coating composition (1) was prepared. In Example 1 (3. Formation of a film), the coating composition (4) was used instead of the coating composition (1), and the non-solvent in the water tank was a mixed aqueous solution of 70% ion-exchanged water and 30% N-methyl-2-pyrrolidone instead of ion-exchanged water. The shear rate was 50 s -1 A diaphragm (4) was produced in the same manner, except that the diaphragm was coated with a 17,000 mPa s viscosity at the time of coating and allowed to stand in ion-exchanged water for 10 minutes after solidification. The thickness of the resulting diaphragm (4) was 200 μm. The content of macrovoids with a major axis of 30 μm or more was 13%, and the air permeability per unit thickness was 1.2. The membrane resistance ratio before and after the hot alkali durability test was 0.84, and the mass loss rate after ultrasonic irradiation was 0.8%.
[0174] [Example 5] A coating composition (5) was prepared in the same manner as in Example 1 (1. Preparation of inorganic particle dispersion), except that zirconium oxide (manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd., product number UEP) was used instead of magnesium hydroxide, and the solid content was changed to 48% in (2. Preparation of coating composition). A diaphragm (5) was prepared in the same manner as in Example 1 (3. Formation of film), except that the coating composition (5) was used instead of the coating composition (1). -1 The viscosity at 25°C is 19,000 mPa s, and at 250 s -1 The viscosity at 25°C is 6300 mPa s, and -1 The viscosity (25°C) was 250,000 mPa s. The thickness of the obtained diaphragm (5) was 205 μm. The content of macrovoids with a major axis of 30 μm or more was 38%, and the air permeability per unit membrane thickness was 0.6. The membrane resistance ratio before and after the hot alkali durability test was 0.78, and the mass loss rate after ultrasonic irradiation was 1.4%.
[0175] [Example 6] A coating composition (6) was prepared in the same manner as in Example 1 (1. Preparation of inorganic particle dispersion), except that titanium oxide (average particle diameter: 0.5 μm) was used instead of magnesium hydroxide, and the solid content was changed to 48% in (2. Preparation of coating composition). Next, a diaphragm (6) was prepared in the same manner as in Example 1 (3. Formation of film), except that a coating composition (6) was used instead of the coating composition (1). -1 The viscosity at 25°C is 20,000 mPa s, and at 250 s -1 The viscosity at 25°C is 6500 mPa s, and -1 The viscosity (25°C) was 270,000 mPa s. The membrane (6) had a thickness of 225 μm. The content of macrovoids with a major axis of 30 μm or more was 26%, and the air permeability per unit membrane thickness was 0.9. The membrane resistance ratio before and after the hot alkali durability test was 0.81, and the mass loss rate after ultrasonic irradiation was 1.5%.
[0176] [Example 7] A coating composition (7) was prepared in the same manner as in (2. Preparation of coating composition) of Example 1, except that the amount of polysulfone resin was changed to 50 parts by mass. A membrane (7) was produced in the same manner as in (3. Formation of membrane) of Example 1, except that the coating composition (7) was used instead of the coating composition (1). -1 The viscosity at 25°C is 29,000 mPa s, and at 250 s -1 The viscosity at 25°C is 12000 mPa s, and -1 The viscosity at 25°C was 570,000 mPa s. The thickness of the resulting diaphragm (7) was 220 μm. The content of macrovoids with a major axis of 30 μm or more was 3%, and the air permeability per unit membrane thickness was 2.4. The membrane resistance ratio before and after the hot alkali durability test was 0.85, and the mass loss rate after ultrasonic irradiation was 0.7%.
[0177] [Example 8] A coating composition (8) was prepared in the same manner as in Example 1 (2. Preparation of coating liquid of coating composition), except that the solid content was changed to 46%. A film (8) was prepared in the same manner as in Example 1 (3. Formation of coating film), except that the coating composition (8) was used instead of the coating composition (1). -1 The viscosity at 25°C is 15,000 mPa s, and at 250 s -1 The viscosity at 25°C is 5300 mPa s, and the viscosity at 0.1 s -1 The viscosity (at 25°C) was 110,000 mPa s. The thickness of the resulting diaphragm (8) was 240 μm. The content of macrovoids with a major axis of 30 μm or more was 38%, and the air permeability per unit membrane thickness was 0.6. The membrane resistance ratio before and after the hot alkali durability test was 0.77, and the mass loss rate after ultrasonic irradiation was 1.6%.
[0178] [Comparative Example 1] A coating composition (c1) was prepared in the same manner as in Example 1 (2. Preparation of coating composition), except that the solid content was changed to 39%. A membrane (c1) was prepared in the same manner as in Example 1 (3. Formation of coating film), except that the coating composition (c1) was used instead of the coating composition (1). -1 The viscosity at 25°C is 5500 mPa s, and at 250 s -1 The viscosity at 25°C is 2800 mPa s, and -1 The viscosity (25°C) was 70,000 mPa s. The membrane thickness of the obtained diaphragm (c1) was 260 μm. The content of macrovoids with a major axis of 30 μm or more was 45%, and the air permeability per unit membrane thickness was 0.5. The membrane resistance ratio before and after the hot alkali durability test was 0.61, and the mass loss rate after ultrasonic irradiation was 2.2%.
[0179] From the above, it was confirmed that the diaphragms for alkaline water electrolysis of Examples have superior stability of membrane resistance (ionic conductivity) in a hot alkaline solution compared to the diaphragms for alkaline water electrolysis of Comparative Examples. Therefore, it is considered that the diaphragms for alkaline water electrolysis of Examples maintain good ionic conductivity and are capable of producing high-purity hydrogen gas stably for a long period of time.
Claims
1. A porous layer including an organic polymer and inorganic particles, the organic polymer is at least one selected from the group consisting of polysulfone, polyethersulfone, and polyphenylsulfone; the inorganic particles are at least one type selected from the group consisting of magnesium hydroxide, zirconium hydroxide, titanium hydroxide, zirconium oxide, and titanium oxide, the porous layer is a layer that constitutes at least one surface of the diaphragm, and the content of macrovoids having a major axis of 30 µm or more in a cross section in the thickness direction of the porous layer is 40% or less, X represented by the following formula (1) is 0.6 or more, A diaphragm for alkaline water electrolysis, characterized in that when subjected to a hot alkaline durability test described below, it has a membrane resistance ratio represented by the following formula (2) of 0.7 or more and 0.91 or less: X = membrane air permeability (sec) / membrane thickness (μm) (1). Membrane resistance ratio = membrane resistance after 240 hours of immersion / membrane resistance after 24 hours of immersion (2) (Hot alkali durability test) The diaphragm for alkaline water electrolysis is immersed in a 30% KOH aqueous solution and maintained at 90°C. The membrane resistance of the diaphragm for alkaline water electrolysis is measured at room temperature 24 hours and 240 hours after immersion.
2. A method for producing a diaphragm for alkaline water electrolysis according to claim 1, comprising the steps of: Contains organic polymers and inorganic particles, shear rate 10 s -1 The viscosity (25°C) is 30,000 mPa·s or less at a shear rate of 0.1 s -1 1. A method for producing a diaphragm for alkaline water electrolysis, comprising using a composition having a viscosity at 25°C of 100,000 mPa s or more.
3. A method for producing a diaphragm for alkaline water electrolysis according to claim 1, comprising the steps of: Contains organic polymers and inorganic particles, shear rate 0.1 s -1 1. A method for producing a diaphragm for alkaline water electrolysis, comprising: using a composition having a viscosity (25°C) of 100,000 mPa s or more, and applying the composition at a shear rate such that the viscosity of the composition is 30,000 mPa s or less.
Citation Information
Patent Citations
Diaphragm for alkaline water electrolysis, alkaline water electrolysis apparatus, production method of hydrogen, and production method of diaphragm for alkaline water electrolysis
JP2018197398A
Diaphragm for alkaline water electrolysis and production method thereof
JP2020169349A
Diaphragm for use in electrolyzing alkaline water, and method of producing the diaphragm
JP2021004411A
Alkaline water electrolysis separator
JP2022538501A
Diaphragm for alkaline water electrolysis, method for producing same, and method for producing inorganic-organic composite membrane
WO2019021774A1